Al0.15Ga0.85N/GaN Heterostructure Field Effect Transistors (HFET)Device Structure Optimization And Thermal Effects. - Thahab, S M; Abu Hassan, H.; Hassan, Z. (2007)

(untitled)
Al0.15Ga0.85N/GaN heterostructure field effect transistors (HFETs) was simulated by using ISETCAD software with varying substrate type, gate length and source drain resistances.